Bagaimana Keberadaan January Effect di Bursa Asia? - Kamaludin, K (Jurnal Trikonomika, 2010)
January effects have been reported in several international stock markets. This study investigated fourteen countriesâ stock markets in Asia stock markets. The Econometric estimation method in this research is EGARCH, observing data composite index daily period 1997 until 2009. The result in this research is undiscovered in the existence January effect significant. January effect just happening two stocks markets which is; Indonesian and Pakistan. There is indication that January effect beginning is not consistence. Besides it also been found anomalies phenomena existence on national holiday at to amount to Asia stock ï¿½ markets.Thesearephenomenamarkets.Thesearephenomena. These are phenomena as more as recognized with holiday effect.